“Can I Still Accomplish Anything?” Vytautas Kubilius and the Role of Intellectual and Critical Thinking in Nation-Building - Bernotienė, Gintarė; Gudauskas, Renaldas; Landsbergis, Vytautas; Juknevičienė, Rasa; Kubilius, Andrius; Zingeris, Emanuelis; Mitaitė, Donata; Ališauskas, Vytautas; Peluritis, Laurynas (Colloquia, 2024)
-